National and Organizational Culture Differences and International Joint Venture Performance - Pothukuchi, Vijay; Damanpour, Fariborz; Choi, Jaepil; Chen, Chao C.; Ho Park, Seung (Journal of International Business Studies, 2002)
This study examines the effect of dimensions of national and organizational culture differences on international joint venture (IJV) performance. Based on data from a survey of executives from joint ventures between Indian partners and partners from other countries, we found that the presumed negative effect from culture distance on IJV performance originates more from differences in organizational culture than from differences in national culture.